Farmácia clínica em unidade de terapia intensiva: identificação, resolução e prevenção de erros de medicação - Adriano, Liana Silveira (2016)
The complexity of care in Intensive Care Units (ICUs) exposes critically ill patients to a high risk of Adverse Drug Events, with the occurrence of Medication Errors being prevalent. The present study aimed to analyze the clinical pharmacy activities performed in the ICU of a hospital of medium and high private complexity and the results achieved in the identification, resolution and prevention of MS. This is a prospective study with an analytical approach in which the incidence, type, severity and factors associated with MS identified during the analysis of prescriptions, performed from February to July / 2016, and during the Medicinal Conciliation ( CM), carried out from April to June / 2016. Patients who had the prescription or CM performed by the pharmacist during the established period were included. The results achieved with the Pharmaceutical Interventions (FI) were verified. The SPSS and Stata programs were used to analyze the data. Categorical variables were compared using the chi-square or Fisher's exact test. A value of p <0.05 was considered statistically significant. To estimate factors associated with MS, a logistic regression was performed, with odds ratio and confidence interval (CI) calculation (95%). The study was approved by the institution's Research Ethics Committee. Analyzes of 1,502 prescriptions were performed, totaling 465 patients. The incidence of MS in this stage was 77.3 (95% CI 55.5-99.1) per 1,000 patient-days. Regarding severity, 59.6% (n = 199) of the errors reached the patient, did not cause damage, but required monitoring. The main MS identified was drug-drug interaction (44.6%, n = 149), followed by preparation, handling or packaging errors (18%, n = 60) and overdose (11.1%, n = 37) . A total of 334 IFs were performed and 79.3% (n = 265) were accepted. The occurrence of MS was significantly associated with: length of hospital stay before ICU admission> 5 days; Length of stay in the ICU> 5 days; Type of nutrition, use of mechanical ventilation, hemodialysis, number of drugs> 10, number of injectable drugs> 10, use of antimicrobials, vasoactive drugs, analgesics and sedatives. A total of 136 patients were admitted to the study, of whom 126 (92.6%) used at least one medication. The incidence of medication errors at this stage was 16.3% (95% CI 11.5-21.2). 128 IF and 71.1% (n = 91) were accepted. As to severity, 65.5% (n = 80) of the errors reached the patient, but there was no damage. The risk factors for the occurrence of medication errors in the conciliation were: age ≥ 60 years, number of comorbidities> 1 and previous use of 9 or more drugs. The study made it possible to identify the type, severity, incidence and factors associated with the occurrence of MS in the ICU. It was verified that the clinical pharmacist's performance is well accepted and contributes to the resolution, prevention and monitoring of medication errors, focusing on patient safety. patient.